THE IMPACT OF DIFFERENCES IN SLAUGHTERING TIME ON OFFALS OF BROILER CHICKEN MAINTAINED WITH A CLOSED HOUSE SYSTEM - I N. T., ARIANA; ., BULKAINI (Majalah Ilmiah Peternakan; Vol 24 No 3 (2021): Vol. 24 No. 3 (2021)DO - 10.24843/MIP.2021.v24.i03.p07, 2021)
This study aims to determine the impact of the difference in cutting time on the weight of offals (internal offals and external offals). The study used a completely randomized design (CRD) with three treatments and six replica- tions. The treatments were: Slaughter on the first day (W1), slaughter on the second day (W2) and slaughter on the third day (W3). The results of the study were that broiler chickens reared in a closed house system and slaughtered on the second and third days experienced a decrease in internal offals weight in the liver by 8.50 – 18.91% and on internal fat 36.74 – 60.77% (P<0.05). The difference in slaughter time did not cause a decrease in internal offal weight in the heart, intestines and gallbladder weight (P>0.05). External offals on the neck there was a weight loss of 4.01 – 8.04% as a result of the difference in slaughter time of 2 – 3 days (P<0.05). The difference in slaughter time had no impact on head weight and foot weight (P>0.05). The conclusion of this study is that the difference in slaughter time of 1-3 days causes a decrease in liver weight and internal fat (internal offals) and a decrease in neck weight (eksternal offals).